2021
DOI: 10.1080/14786419.2021.2021517
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities and HPLC analysis of secondary metabolites of a morphologically identified endophytic Aspergillus fungus isolated from Mangifera indica

Abstract: Natural products from Nigerian plants are significant in the search for drug compounds, as they contribute new compounds with biological properties to the fight against resistant pathogens, hence the study. Fresh leaves of M. indica were prepared for fungal isolation, identification, fermentation, and secondary metabolites extraction. The extract, subjected to HPLC analysis revealed presence of two bioactive compounds: p-Hydroxylbenzoic acid, and Protocatechuic acid. The extract exhibited antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Meanwhile, Padhi et al [ 21 ] revealed that A. niger metabolites showed antifungal activity against Candida albicans with IC 50 31 mg/mL, and antibacterial activity against Pseudomonas aeruginosa , Escherichia coli and Staphylococcus aureus with IC 50 of 160 mg/mL, 47 mg/mL and 135 mg/mL, respectively. Chigozie et al [ 22 ] reported that the fungal extract of Aspergillus sp. isolated from fresh leaves of Mangifera indica .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Padhi et al [ 21 ] revealed that A. niger metabolites showed antifungal activity against Candida albicans with IC 50 31 mg/mL, and antibacterial activity against Pseudomonas aeruginosa , Escherichia coli and Staphylococcus aureus with IC 50 of 160 mg/mL, 47 mg/mL and 135 mg/mL, respectively. Chigozie et al [ 22 ] reported that the fungal extract of Aspergillus sp. isolated from fresh leaves of Mangifera indica .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, EPF exhibited direct antagonism against pathogens via antibiosis, competition, or parasitism through the production of fungal secondary metabolites ( Ownley et al, 2008 ; Vega et al, 2009 ). Previous research has found that Aspergillus species could produce various beneficial compounds such as cyclosporine A, asperfuranone, terrrein, itaconic acid, kojic acid, citric acid, and gluconic acid ( Sun et al, 2018 ; Wu et al, 2019 ; Chigozie et al, 2022 ), which showed antifungal, antibacterial, and phytotoxic activities, and played a crucial role to antagonize the devastating phytopathogens ( Ding et al, 2019 ). It was found that A. versicolor had the ability to inhibit the destructive phytopathogen Macrophomina phaseolina .…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes are classified base don he type of microbe and includes fungi, bacteria and actinomyces (9). Recent research according to several reports has shown that Nigerian medicinal plants are undeniably sources of novel endophytic fungus with huge potential to produce novel bioactive lead compounds yet untapped (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%